The Effect Of Intellectual Humility, Multicultural Personality, and Religious Orientation Toward Religious Tolerance On Students Of UIN Syarif Hidayatullah Jakarta - Arif Budiman Al Fariz; Gazi Saloom (Psikis : Jurnal Psikologi Islami, 2021)
This study aims to determine the influence of intellectual humility, multicultural personality (cultural empathy, open-mindedness, emotional stability, flexibility, and social initiative), religious orientation (quest religiousness, intrinsic religiousness, and extrinsic religiousness) toward religious tolerance on students of the Syarif Hidayatullah State Islamic University of Jakarta. Participants in this study involved 360 students using non-probability sampling as a sampling technique. As for religious tolerance measuring instrument uses a measuring instrument from RT Witenberg`s theory with modified into the scale. The intellectual humility variable uses the Comprehensive Intellectual Humility Scale (CHIS), the multicultural personality variable uses the Multicultural Personality Questionnaire Short Form (the MPQ-SF) and the religious orientation variable uses the Introduction to the New Indices of Religious Orientation (NIRO). The findings show a significant influence between intellectual humility, multicultural personality, and religious orientation toward religious tolerance with a proportion of variance of about 51%. The four significant variables are intellectual humility, cultural empathy, open-mindedness, intrinsic religiousness. While the influence of emotional stability, flexibility, social initiative, quest religiousness, and extrinsic religiousness has no significant effect. multicultural personality and religious orientation toward religious tolerance with a proportion of variance of about 51%. The four significant variables are intellectual humility, cultural empathy, open-mindedness, intrinsic religiousness. While the influence of emotional stability, flexibility, social initiative, quest religiousness, and extrinsic religiousness has no significant effect. multicultural personality and religious orientation toward religious tolerance with a proportion of variance of about 51%. The four significant variables are intellectual humility, cultural empathy, open-mindedness, intrinsic religiousness. While the influence of emotional stability, flexibility, social initiative, quest religiousness, and extrinsic religiousness has no significant effect.